2018
DOI: 10.1364/oe.26.004738
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the magneto-optical Kerr effect through the use of a plasmonic antenna

Abstract: We employ an extended finite-element model as a design tool capable of incorporating the interaction between plasmonic antennas and magneto-optical effects, specifically the magneto-optical Kerr effect (MOKE). We first test our model in the absence of an antenna and show that for a semi-infinite thin-film, good agreement is obtained between our finite-element model and analytical calculations. The addition of a plasmonic antenna is shown to yield a wavelength dependent enhancement of the MOKE. The antenna geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Plasmonic metasurfaces have been employed for other second-order processes like sum-frequency generation (SFG) 66 , 67 and difference-frequency generation (DFG) 68 70 In contrast, third-order nonlinear effects, such as the Kerr effect, 71 73 third-harmonic generation (THG), 29 , 31 , 74 77 and four-wave mixing (FWM), 23 , 25 , 78 83 are free from symmetry considerations for linear polarized light. In addition, high-harmonic generation 84 and supercontinuum white-light generation 32 have also been realized using plasmonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic metasurfaces have been employed for other second-order processes like sum-frequency generation (SFG) 66 , 67 and difference-frequency generation (DFG) 68 70 In contrast, third-order nonlinear effects, such as the Kerr effect, 71 73 third-harmonic generation (THG), 29 , 31 , 74 77 and four-wave mixing (FWM), 23 , 25 , 78 83 are free from symmetry considerations for linear polarized light. In addition, high-harmonic generation 84 and supercontinuum white-light generation 32 have also been realized using plasmonic nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetooptical Kerr effect (MOKE) has potential application in ultrathin magnetic devices, e.g. films [8], multilayers [9], and magnetic superlattices [10], and, the surface magneto-optic Kerr effect (SMOKE) has remain a powerful tool for in situ characterization [11] . All the setups have shown bistability as their predominant characteristics which causes due to nonlinear susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that a plasmonic cover of the transparent films significantly modifies their magneto-optical response, and the Faraday and transverse Kerr effects are resonantly enhanced by several orders of magnitude. The concept of the magnetic field measurement based on the transverse Kerr effect in a magnetoplasmonic nanostructure with graphene layer was proposed theoretically . However, magnetoplasmonic magnetometry has not been demonstrated yet.…”
mentioning
confidence: 99%